2019
DOI: 10.1111/ajt.15024
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective reperfusion strategies differentially affect mitochondria: Studies in an isolated rat heart model of donation after circulatory death (DCD)

Abstract: Donation after circulatory death (DCD) holds great promise for improving cardiac graft availability; however, concerns persist regarding injury following warm ischemia, after donor circulatory arrest, and subsequent reperfusion. Application of preischemic treatments is limited for ethical reasons; thus, cardioprotective strategies applied at graft procurement (reperfusion) are of particular importance in optimizing graft quality. Given the key role of mitochondria in cardiac ischemia-reperfusion injury, we hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
(84 reference statements)
1
12
0
Order By: Relevance
“…Importantly, MPC can inhibit irreversible opening of the mitochondrial permeability transition pore (mPTP), which is associated with the release of cytochrome c and the collapse of the membrane potential and leads to cell death [43,44]. We have previously reported that MPC-induced cardioprotection is associated with improved mitochondrial function (greater complex I activity and ATP content and less cyt c release) in a similar model, therefore supporting the concept of MPC-induced mitochondrial preservation [45]. Interestingly, evidence exists to support a role for AMPK in the inhibition of mPTP opening [32], which is consistent with a role for AMPK in the cardioprotection observed in HiR MPC hearts.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Importantly, MPC can inhibit irreversible opening of the mitochondrial permeability transition pore (mPTP), which is associated with the release of cytochrome c and the collapse of the membrane potential and leads to cell death [43,44]. We have previously reported that MPC-induced cardioprotection is associated with improved mitochondrial function (greater complex I activity and ATP content and less cyt c release) in a similar model, therefore supporting the concept of MPC-induced mitochondrial preservation [45]. Interestingly, evidence exists to support a role for AMPK in the inhibition of mPTP opening [32], which is consistent with a role for AMPK in the cardioprotection observed in HiR MPC hearts.…”
Section: Discussionmentioning
confidence: 74%
“…An isolated heart model of DCD heart transplantation was used, as previously reported [26,45,47,53,54], with male Wistar rats (Janvier Labs, Le Genest-Saint-Isle, France) of 10 to 11 weeks of age to ensure mature cardiac metabolism [55] and to represent young, adult human DCD donors. Rats were housed under standard conditions at a controlled room temperature with a 12-h light-dark cycle and access to water and food ad libitum.…”
Section: Isolated Heart Perfusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-established isolated rat heart model of DCD was used (16,(28)(29)(30)(31). Male Wistar rats (Janvier Labs, Le Genest-Saint-Isle, France) aged 11-12 weeks were used to ensure mature cardiac metabolism (32) and to represent young, adult human DCD donors.…”
Section: Isolated Heart Perfusionsmentioning
confidence: 99%
“…Defective mitophagy has been observed in cardiac I/R injury, and is associated with mitochondrial dysfunction in cardiomyocytes and cardiac microvascular endothelial cells [15,16]. Similarly, mitochondrial biogenesis was found to be inhibited in a mouse model of cardiac I/R injury; thus, improving mitochondrial biogenesis is considered to be a promising method of alleviating cardiac I/R injury [17,18]. However, there is not yet an effective drug to promote mitochondrial biogenesis in the heart.…”
Section: Introductionmentioning
confidence: 99%